2019
DOI: 10.1136/bmj.l1613
|View full text |Cite
|
Sign up to set email alerts
|

Probable carcinogenicity of glyphosate

Abstract: Independent investigation must continue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…In recent years, there has been an increasing amount of literature focusing on the evaluation procedures for regulatory risk assessment of pesticides [ 17 , 18 , 19 , 20 ]. Particular discussion points include that chronic pesticide studies are only on the active ingredient (i.e., technical glyphosate) and the requirement for more real-world exposure data on the formulated glyphosate products, due to the combined effects on the toxicity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, there has been an increasing amount of literature focusing on the evaluation procedures for regulatory risk assessment of pesticides [ 17 , 18 , 19 , 20 ]. Particular discussion points include that chronic pesticide studies are only on the active ingredient (i.e., technical glyphosate) and the requirement for more real-world exposure data on the formulated glyphosate products, due to the combined effects on the toxicity [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A jury in California ordered Monsanto to pay more than $2bn (£1.54bn; €1.78bn) to a couple who developed non-Hodgkin’s lymphoma after using the weedkiller Roundup, which contains glyphosate—identified as a probable human carcinogen by the World Health Organization’s International Agency for Research on Cancer 4. The victory for Alva and Alberta Pilliod is the third verdict against Monsanto, which is now owned by Bayer.…”
Section: Glyphosatementioning
confidence: 99%
“…Therefore, non-target organisms such as humans are most susceptible to GBH exposure, resulting in various health issues ( Turkmen et al, 2019 , Samsel and Seneff, 2013 ). In 2015, the World Health Organization’s International Agency for Research on Cancer (IARC), identified glyphosate as group 2A chemical – whose constituents have probable carcinogenic effects on humans ( Kogevinas, 2019 , Tarazona et al, 2017 ). Across the globe and in particular Africa, use of herbicides to control weeds is rampant in the absence of vital data on their composition and safety.…”
Section: Introductionmentioning
confidence: 99%